Penjatuhan Putusan Hakim Di Bawah Batas Minimum Khusus Dalam Tindak Pidana Korupsi - Mulyani, Ade Desti; Deliana, Evi; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Efforts to eradicate corruption have become a global problem, no longer a regional one. The main problem is that corruption increases along with advances in prosperity and technology. Law enforcement in criminal acts of corruption is not optimal because the verdicts of judges in corruption cases still disappoint the public but benefit or make the corruptors happy.In practice, there is a verdict from a judge in adjudicating a criminal act of corruption that imposes a criminal threat on the defendant by breaking through the special minimum rules as stipulated in the Corruption Eradication Law, namely in decision Number 196 K/Pid/Sus/2007 and Decision Number 2399 K/Pid.Sus/2010.This type of research can be classified as normative, this research is a study of legal principles related to juridical analysis of the Decision Number 196 K/Pid/Sus/2007 and Decision Number 2399 K/Pid.Sus/2010 which impose decisions below the special minimum limit. Data sources are supported by secondary data sources which consist of 3 legal materials, namely: primary legal materials, secondary legal materials, tertiary legal materials. The data collection technique is literature review.Keywords: Penjatuhan Putusan Hakim - Bawah Batas Minimum Khusus -Tindak Pidana Korupsi